Dioximate‐ and Bis(salicylaldiminate)‐Bridged Titanium and Zirconium Alkoxides: Structure Elucidation by Mass Spectrometry. Issue 4 (27th February 2013) - Maurer, Christian; Pittenauer, Ernst; Puchberger, Michael; Allmaier, Günter; Schubert, Ulrich
Abstract The treatment of titanium alkoxides with 1, 5‐pentanedioxime or 2, 5‐hexanedioxime resulted in the formation of complexes [{TiL(OR)2}2] in which the dioximate ligands (L) bridge a dimeric Ti2(μ2‐OR)2 unit. The structures of the complexes were determined by single‐crystal structure analysis, ESI mass spectrometry, and 1D and 2D solution NMR spectroscopy. In contrast, the treatment of titanium alkoxides with dioximes bearing cyclic linkers, such as cyclohexyl or aryl groups, resulted in insoluble polymeric compounds. The treatment of various bis(salicylaldiminates) with titanium and zirconium alkoxides resulted in compounds with the same composition [{TiL(OR)2}2], in which, however, two monomeric Ti(OR)2 units are bridged by the ligands L. The two structural possibilities can be distinguished by low‐energy collision‐induced dissociation owing to their different fragmentation patterns.